Formation of Calcium Oxalate Patinas as Protective Layer on Basaltic Stone Surfaces of 17th Century Raigad Hill Fort, India - Manager Rajdeo Singh; Rajendra Yadav (Heritage, 2023)
This work reports calcium oxalate film formation on basaltic stone surfaces of the 17th-century western India Raigad Hill Fort. Nine stone samples extracted from the exterior surfaces of different historical structures of the fort were investigated under FTIR, optical microscopy, XRD, and SEM-EDX. The FTIR spectroscopy revealed intense peaks for Ca-oxalate patinas on basaltic stone surfaces. Observation under optical microscopy clearly showed milky white oxalate films, and peaks for crystalline calcium oxalate, including rock silicates, were prominently observed through XRD investigations. The surface morphology, the origin of the oxalate film, and the state of conservation of the basalt rock were investigated through SEM-EDX. The massive structures at Raigad, at a height of about 800 m, have hardly been chemically cleaned or coated with preservatives in the past. The presence of organic filaments in SEM photomicrographs indicated the biological origin of the oxalate patina due to the thick growth of microbiota on the monument stone during very heavy monsoons. The oxalic acid secreted by microbes dislodged the Ca-rich plagioclase of the stone, ensuring Ca-ions’ availability for film formation. The optical and mineralogical analyses suggest that the film is not the result of simple deposition but of the surface transformation of basaltic stone.